INCREASING THE GROWTH OF PT PASAR MURAH NUSANTARA THROUGH THE 3B STRATEGY: BUILD, BORROW AND BUY - Kusumawati, Dineke
Indonesia, as a country with a very large population and is currently experiencing a very rapid rate of population growth, naturally creates extraordinary pressure on the availability and sustainability of natural resources. On the other hand, Indonesia is also blessed with abundant natural wealth ranging from agricultural to marine products, which actually really supports efforts to increase mass food production to meet domestic consumption needs. In recent years, there has been a shift in Indonesian people's food and daily necessities shopping patterns from traditional shopping at markets or grocery stores, switching to digital e-grocery or online retail channels. This phenomenon certainly opens up market opportunities and extraordinary growth potential for brave retail business pioneers such as PT Pasar Murah Nusantara who are here to take advantage of this opportunity. However, after operating for one year, it turned out that PT. Pasar Murah Nusantara was facing a number of obstacles that hampered its business aspirations, including low product variety, lack of employees, low brand, low promotion, limited coverage, limited capital, and not yet integrated platform. Overcoming this can enable PT. Pasar Murah Nusantara to take advantage of changes in consumer demand in Indonesia by increasing its e-grocery proposition. This research uses a mixed-method approach, combining qualitative (In-Deep Interview) and quantitative (questionnaire) methods to gain a deeper understanding of the growth potential of PT. Pasar Murah Nusantara. Mixed-method research is research that combines descriptive elements, providing a comprehensive picture of the internal and external environment of PT. Pasar Murah Nusantara, thus allowing for recommendations for growth strategies based on quantitative and qualitative insights. Qualitative research, which focuses on individual knowledge and experience, is conducted through In-depth Interviews with experts. Quantitative research, which involves analysis, uses questionnaires addressed to customers to gather customer satisfaction. The analysis in this research is divided into two, namely internal analysis and external analysis. Internal analysis uses Marketing Resources, STP (Segtemneting, Targeting, and Positioning, internal analysis aims to find out what the internal conditions of PT. Pasar Murah Nusantara are currently. External analysis uses Customer Analysis, external analysis aims to find out what the external conditions are, namely to measure customer satisfaction Pasar Murah This internal and external analysis is then combined into SWOT (Strength, Weakness, Opportinities, and Threats) to combine whatever internal and external influences exist for the future growth of Pasar Murah's business. From the results of the SWOT (Strength, Weakness, ii Opportinities, and Threats) analysis obtained then a 3B strategy formulation (Build, Borrow and Buy) is carried out. The results of the 3B strategy formulation carried out in this research recommend "Borrow Strategy" as the most possible way forward. This strategy utilizes collaboration with strategic partners to obtain resources and skills required. With the presence of technology providers and experienced organizations, Bargain Market can overcome its investment weaknesses without a significant head start. This approach allows for faster technology acquisition, expanded product variety, expanded location coverage, and ultimately, improved customer experience. This research outlines a detailed implementation plan for the Borrow Strategy including specific recommendations for identification and initiation with other, more experienced companies. This roadmap provides clear direction for Pasar Murah to execute its growth strategy and unlock its full potential. By implementing Borrow Strategy, Pasar Murah can overcome its limitations, accelerate its growth, and strengthen its position as a leading food ingredients supplier.